Antimicrobial susceptibility of dominant Salmonella serovars, isolated in North-West federal district in 2004–2018 from different sourses - A. V. Zabrovskaia; S. A. Egorova; N. A. Antipova; E. V. Smirnova; L. I. Semchenkova; T. E. Bystraya; S. Е. Sokolnik; N. P. Utkina; L. Y. Sikhando; N. V. Satosova (Журнал инфектологии)
Objective: Comparative analysis of antimicrobial resistance of S. Enteritidis, S. Infantis, and S. Typhimurium isolated from humans, farm animals, and animal products.Materials and methods. 898 Salmonella strains isolated from humans (673), farm animals (132), and animal products (93) were studied. Antimicrobial susceptibility was determined according to the EUCAST recommendations. The detection of beta-lactamase genes was performed by PCR. The mutations in the QRDR region of the gyrA gene were determined by amplification and direct sequencing of the internal fragment of the gene.Results. Antimicrobial resistance in 69,9% of strains isolated from humans, 78,5% – from food, and 88,6% – from farm animals was detected. 68,7% of S. Enteritidis strains isolated from humans, 61,4% from food, and 21,1% isolated from animals were resistant to quinolones. The proportion of MDR S. Typhimurium strains ranged from 21,6% to 88,2%, depending on the source of isolation. From the S. Infantis strains 89,3% of strains isolated from humans, 94,5% – from animals and 97,8% – from food were resistant to antimicrobials, 67,9% of strains isolated from humans, 80,0% – from food and 89,0% ‒ from animals were MDR. The production of beta-lactamases TEM-1, CTX-M1, CTX-M2, and CMY-2 was detected. Resistance to quinolones was determined by a chromosomal mechanism: single-nucleotide substitutions in the gyrA gene were identified: Asp87Tyr, Ser83Phe, Asp87Asn, Ser83Tyr.Conclusion. Antimicrobial susceptibility in Salmonella of dominant serovars had specific traits. Strains isolated from animals differed significantly from strains from humans and animal products. Resistance to quinolones and beta-lactams in Salmonella, regardless of the source of isolation and serovar, was due to molecular mechanisms universal for Enterobacteriacae.